Presisi Metode Penentuan Arah KiblatPresisi Metode Penentuan Arah Kiblat: (Studi Komparasi Ulama Pesantren Probolinggo) - Ahmad Fiqri Syaikal; Bashori Alwi; Moh Ziad Farhan Fahri; Muhajir, Muhajir (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2024)
Qibla is the direction that Muslims aim for in carrying out worship, especially prayer, which is facing the direction of the Kaaba at the Grand Mosque, especially prayer, which is facing the Kaaba at the Grand Mosque, this is based on the arguments of the Qur'an based on the arguments of the Qur'an; Al-Baqarah: 148-150, then based on these arguments then facing the Qibla in praying is obligatory and one's prayer is not valid if one does not face the Qibla intentionally, but what is the view of pesantren scholars in Probolinggo on this ka'bah issue and how to respond to several places of prayer that are not in accordance with the actual direction of the Qibla. This research uses an empirical method with a qualitative approach, which explores the opinions of pesantren scholars in Probolinggo about the Qibla direction and how they respond to several places of worship, as well as how they respond to several places of worship that do not face the direction of the ka'bah. This method is used to obtain natural data generated from interviews as well as some supporting data related to Qibla direction. This research seeks to provide an understanding of the Qibla direction in detail, as well as the differences in the attitudes of the Probolinggo Islamic boarding school ulama towards several places of worship that do not face the Qibla direction.